Замки Закарпатья второй половины ХІІІ – первой половины XIV вв. - Калініченко, Віталій; Прохненко, Ігор; Жиленко, Марія (Chişinău, Chişinău: Muzeul Național de Istorie a Moldovei, 2021)
Four successive stages can be identified in the history of functioning of the castles of Hungarian Kingdom. A system of the royal counties, with the ispans’ (counts’) fortifications in their core, was distinctive for 12-13-th centuries. Small, newly built noble castles appeared here since 13-th centuries. During the Arpads they turned into important tools of influence in the hands of certain oligarchic clans. When House of Anjou strengthened its graspon Hungarian throne, the castles became an expression of political power of monarch and functioned mainly as the centers of royal domains. During the Late Middle Ages they were gradually taken over by new nobility and often transformed into well-developed complexes, residencies. The first fortifications of the new type were built in the region, unpopulated areas were granted to minor nobility and German settlers were invited in a wake of Bela IV centralized policy of colonization and castles construction. There were three main stages of the Late Middle Ages and Early Modern Period castle architecture on the territory of Zakarpatska oblast of Ukraine. Two of them are presented by the fortifications of second half of 13-th and the first half of 14-th centuries. Typically just a small part of these sites was occupied by fortifications. Usually they had a thin cultural layer. These features argues for their predominantly watch and representation functions. The sites of the first chronological group (13-th century) stopped to exist at the edge of 13-th-14-th centuries and they never used as fortifications again. By contrast, the castle complexes of the first half of 14th century formed the basis for a system of fortifications in North-Eastern Hungary of the end of 14th - beginning of 16-th centuries. However their early cultural layers were almost completely destroyed in a wake of radical re-building.
Castelele Transcarpatiei din a doua jumătate a sec. XIII – prima jumătate a sec. XIV
The castles of Transcarpathia of the second half of 13-th – first half of 14-th centuries
Keywords: Северо-Восточная Венгрия; Закарпатье; укреплённые поселения; замки; фортификации; башни; каменные стены; Средневековье